280 Rapid response to itraconazole and transcript analysis of the cervical cancer tissue obtained by the sequential biopsy: a case report. (13th November 2020) - Takimoto, Y; Isono, R; Ishikawa, E; Ueda, T; Inoue, K; Sakata, K; Nakagomi, N; Tsubamoto, H; Shibahara, H
Abstract : We have been studying drug repositioning of itraconazole for an anticancer drug, and in vitro study demonstrated itraconazole inhibited growth of cervical cancer cells via down regulation of Akt/mTOR, hedgehog, and Wnt/β-catenin signal transduction. We report a case who showed rapid response to itraconazole and transcript analysis of the sequential biopsy was conducted. [Case] A 75-year-old woman with cervical cancer, diagnosed with Stage IIIB (cT3C N0 MA) squamous cell carcinoma was enrolled in a window of opportunity clinical trial (jRCTs051190006). She had 40 mg of oral itraconazole daily for 7 days before the primary treatment started (a window period). Her symptom of vaginal bleeding decreased and the vaginal ultrasound showed the maximum diameter of the cervical tumor decreased from 61 mm to 50 mm. The primary treatment involved pelvic external beam radiation therapy (54Gy/30fr) combined with chemotherapy (40 mg/m2 of cisplatin, weekly x 5 times) and a brachytherapy boost (24 Gy/4fr). Four months after last administration of cisplatin, she had pelvic, mediastinal and supraclavicular lymph node recurrence. Tumor genomic profiling using FoundationOne CDx showed PIK3CA and PTEN mutation, microsatellite stable, and tumor mutation burden of 23Muts/Mb. In Japan, pembrolizumab was not covered by public insurance. She wished further treatment with itraconazole. Transcript analysis of mRNA obtained before and after itraconazole treatment during the initial window period are shown in table 1 . Pathway mapping using Transcriptome Analysis Console version 4.0 (Thermo Fisher Scientific) showed significant reduction of PI3K-Akt-mTOR signaling pathway.